What is Right About Bankruptcy Law and Wrong About Its Critics - Samuel L. Bufford (Washington University Law Quarterly, 1994)
My comments in this paper focus on the papers in this Symposium by Professors Barry Adler; James Bowers; and Philippe Aghion, Oliver Hart and John Moore (Aghion-Hart-Moore) I argue that the central points of these papers are gravely mistaken because they completely misunderstand the character of the bankruptcy caseload and procedures, they ignore some important purposes of bankruptcy reorganization, and they misstate the success rate for reorganizations. I have chosen these papers for comment for two reasons: they recommend radical changes in bankruptcy law, and they are based on the thinnest knowledge of bankruptcy practice. Incidentally, they also all take an economics approach to law.
Keywords: Bankruptcy law; United States; Bankruptcy reorganization